Membangun Fondasi Keilmuan Ekonomi Islam: Telaah Metodologi Muhammad Akram Khan - Ahmad Ubaidillah (JES (Jurnal Ekonomi Syariah), 2017)
Throughout my experience in tracking down and reading books on faith-based economics, in this case Islam, there are no books that specifically list the title of "Islamic economics". If there is, it is only initiated or introduced. Most books coming down to us still use the titles starting with the word, for example, system, concept, principle, or the doctrine of Islamic economics. Why do the authors of the book Islamic economics seem not dared to give his book title with label "science"? I presume that Islamic economics has not been considered as a science. In building a science, methodology is required. Islamic Economics also requires a well-established methodology to build the foundation of science. The study answers questions; how is methodology which is offered by Muhammad Akram Khan to build Islamic economics. The method used in this research is the study of literature with qualitative approach.The result of study concludes that Khan offers methodology of Islamic economics, if summarized, written as follows: First, Islamic economics uses a framework derived from the texts of divinity (revelation). Second, Islamic economics uses the inductive method, which gives witness to the truth or falsity assumptions and predictions about the two criteria of rationality and empirical evidence. Third, Islamic economy is built on ethical values such as justice, virtue, moderation, sacrifice, caring for others, in the analysis, as behavioral parameters. Fourth, Islamic economics is a normative discipline. Islamic Economics investigates ways and means to change the existing economy with Islamic economy. Fifth, Islamic economics ask different questions with conventional economics. Its attention is on welfare (falah) human and creating social and institutional conditions that maximize falah in society. Clearly, Islamic economics strongly supports research programs that help maximize falah. Furthermore, Khan elaborates several issues related to the methodology that often appears in the forum of Islamic economists. There are some problems that Khan proposes, they are the interaction with modern economics, the role of revelation, assuming ideal Islamic society, and the general theory of Islamic economics. Keywords:  Islamic Economics, Methodology, Muhammad Akram Khan